Penerapan Metode Peramalan Produksi dan Perencanaan Kebutuhan Bahan Baku Dengan Metode Material Requirement Planning di PT.CJ Feed Medan - Yufri Alrahman; Kamil Mustafa; Yuana Delvika (JOURNAL OF INDUSTRIAL AND MANUFACTURE ENGINEERING, 2017)
PT. CJ Feed Medan is a engaged in the animal feed industry. The purpose of this study is to determine the amount of GM-1C feed production from the forecasting of the number of sales of animal feed products of the previous type. And to plan raw material inventory for production of GM-1C animal feed with Material Requirement Planning method. Forecasting is a process to estimate the level of some future needs that include the needs in quantity size, quality, time and location required in order to meet the demand for goods or services. Material Requirement Planning is a logical procedure, decision rule and computerized records engineering designed to translate master production schedules or MPS (Master Production Scheduling) into Net Requirements for all items or components. From good sales data forecasting method is cyclical method because it has the smallest SEE value. So it can be estimated sales of the last 10 days in October 2017 as much as 70782, 70143, 69266, 68210, 67049, 65860, 64725, 63720, 62915 and 62365. The last process to get data on raw material needs is the making of MRP report. This report is a comprehensive report of the raw material requirements for GM-1C products.